PENTINGNYA INOVASI PRODUK DEMI KEBERLANGSUNGAN UMKM (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract The purpose of community service is to provide an understanding of knowledge about product innovation and provide knowledge about strategies for carrying out product innovation for the sustainability of MSMEs. Product innovation efforts can be in the form of utilizing useless materials to be useful, such as: dragon fruit skin can be made into healthy and fresh drinks and can also change the variant, shape, size, taste, etc. This is because it meets the needs and desires of consumers who are constantly changing. Therefore, product innovation is needed for the sustainability of MSMEs. Product innovation is an innovation in products, the process of making products that are better than previous versions or developing existing products. The goals of product innovation include improving product quality, meeting customer demand, creating new markets amidst existing competition, replacing products. The target of this community service is the members and chair of the Yasinta KUB, Sokawera Village, Cilongok District, Banyumas Regency. The method used is the lecture method from the community service team, the practice of cooking dragon fruit skin into healthy and fresh drinks and providing assistance for additional capital to help purchase raw materials, such as: dragon fruit, lime, granulated sugar, glass cups, etc. The result of the service is that the members and chairman of KUB Yasinta, Sokawera Village, Cilongok District, Banyumas Regency understand the importance of product innovation, strategies for carrying out product innovation for the sustainability of MSMEs and providing assistance for purchasing raw materials. The service team was happily received by the chairman and members of KUB Yasinta Cilongok